The influence of project-based learning using PhET on fifth-grade scientific literacy in electrical circuits - Saras Dwi Putri Maulida; Mubarak Ahmad (Universitas Papua, 2026)
This study aims to investigate the effect of the Project Based Learning (PjBL) model assisted by PhET simulations on the scientific literacy skills of fifth-grade elementary school students, specifically on the topic of electrical circuits. The study employed a quasi-experimental method with a nonequivalent control group pretest-posttest design, conducted at a public elementary school in East Jakarta. The sample consisted of 61 fifth-grade students divided into two groups: the experimental group and the control group. The instrument used was a scientific literacy test developed based on the four components of scientific literacy according to PISA, namely context, content, competency, and attitude, and it had undergone validity and reliability testing. Data were analyzed using descriptive statistics and an independent t-test. The results showed a significant difference in scientific literacy scores between the experimental and control groups, indicating that the application of the PjBL model with PhET simulations is effective in enhancing the scientific literacy of elementary school students.